Tuberculosis: a rare entity of anal disease - Ho, Hui Lian; Hud Zin; Firdaus Hayati; Nornazirah Azizan; Khasnizal Abd Karim (2017)
"Abstract: Tuberculosis (TB) is a common infectious granulomatous disease in Malaysia, especially Sabah. Anal TB is extremely rare, approximately less than 1% of the cases. It can present as fistula-in-ano, ulcer, stricture, and even mass. The diagnosis can be established via bacteriological, histopathological and molecular methods; even Mantoux test, chest radiography and ESR occasionally are not helpful. Anti-TB medication is the primary line of treatment as surgery alone is inadequate. We present a case of anal TB presented with nodular mass with ulcerated surface mimicking malignancy, our management strategies and review of the literature.